Produção de ácidos graxos poli-insaturados por fermentação submersa - Somacal, Simara (2015)
The objective of this work was the polyunsaturated fatty acids (PUFAs) production by submerged fermentation from the fungus Mortierella isabellina. A Plackett Burman experimental design was designed to evaluate the best conditions for PUFAs production in shake flasks. Three different components of the culture medium (yeast extract, peptone, and sucrose) and three fermentation parameters (agitation, temperature and pH) were evaluated. Analyzing the results of experimental design new assays were performed with increasing concentration of yeast extract. Fermentations were conducted in Erlenmeyer flasks with 10% (v/v) inoculums for 120h, micronutrients ((NH4)2SO4, FeSO4.7H2O, MnSO4.H2O, MgSO4.7H2O) were fixed. The scale up using STR bioreactor with 2.5 L of culture medium and 10% (v/v) inoculums for 120h was defined through better results of Plackett Burman.. A 2² central composite design was set to evaluate the effect of agitation and aeration in fungal biomass production, lipids content and fatty acids profile. The lipid was extracted from dried biomass and the fatty acids were analyzed by gas chromatography. The results of the fermentation in shake flasks showed that only yeast extract had a significant effect (p <0.1) in PUFAs production and this effect was positive. The highest percentage of PUFAs produced (28.17%) was obtained in higher yeast extract concentration (3.75 g / L). Agitation and aeration did not had a significance effect (p <0.1) in the evaluated range, in bioreactor on PUFAs and lipids production. However, agitation had a significant positive effect on biomass production.The presence of fatty acids of family n-3 (α-linolenic acid, eicosapentaenoic acid and docosahexaenoic acid) and n-6 families (linoleic acid and γ-linolenic acid) were observed. Nitrogen source is directly related to increased PUFAs production. The variables agitation and aeration, in the evaluated range, did not influence the PUFAs production. The Mortierella isabellina produced fatty acids n-3 and n-6 family, but additional studies are needed to optimize this production.